ANALYSIS OF AVAILABILITY OF GUIDED INQUIRY MODEL ON LESSON PLANS PHYSICS GRADE XI SEMESTER 1 IN SENIOR HIGH SCHOOLS - Windri Suci Gaitari; Silvi Yulia Sari; Yenni Darvina; - Hufri; Fanni Rahmatina Rahim (Universitas Negeri Padang, 2021)
In the revised 2013 curriculum, students are required to have skills that fit the challenges of the 21st century. To train these skills is to apply the right model in learning, namely the guided inquiry model. The availability of guided inquiry models in learning can be seen from the lesson plans. All lesson plan at public high schools has not been identified whether they have a guided inquiry model. Therefore, this research aims to find out the availability of guided inquiry models in lesson plan Physics grade XI Semester 1 in high schools. This research is descriptive research with a qualitative approach. The population data in this study are all lesson plan Physics High School grade XI semester I used by 15 districts in West Sumatra. The samples in this study were lesson plan Physics in high schools grade XI Semester I from 7 schools created by teachers. Based on the research that has been done, the availability of the guided inquiry model in lesson plan physics grade XI semester 1 obtained the results of the analysis that lesson plan with the highest availability category is lesson plan 3 with a percentage of 83.3% in very available category. The lesson plan with the lowest availability is lesson plan 1 and lesson plan 6 with a percentage of 16.67% in the unavailable category. Thus, it can be concluded that the availability of the guided inquiry model in the lesson plans for grade XI semester 1 is categorized as sufficient available.